PLANT CONSUMPTION BY GRIZZLY BEARS REDUCES BIOMAGNIFICATION OF SALMON‐DERIVED POLYCHLORINATED BIPHENYLS, POLYBROMINATED DIPHENYL ETHERS, AND ORGANOCHLORINE PESTICIDES. (25th March 2013) - Christensen, Jennie R.; Yunker, Mark B.; MacDuffee, Misty; Ross, Peter S.
Abstract The present study characterizes the uptake and loss of persistent organic pollutants (POPs) in grizzly bears (Ursus arctos horribilis) by sampling and analyzing their terrestrial and marine foods and fecal material from a remote coastal watershed in British Columbia, Canada. The authors estimate that grizzly bears consume 341 to 1, 120 µg of polychlorinated biphenyls (PCBs) and 3.9 to 33 µg of polybrominated diphenyl ethers daily in the fall when they have access to an abundant supply of returning salmon. The authors also estimate that POP elimination by grizzly bears through defecation is very low following salmon consumption (typically <2% of intake) but surprisingly high following plant consumption (>100% for PCBs and organochlorine pesticides). Excretion of individual POPs is largely driven by a combination of fugacity (differences between bear and food concentrations) and the digestibility of the food. The results of the present study are substantiated by a principal components analysis, which also demonstrates a strong role for log KOW in governing the excretion of different POPs in grizzly bears. Collectively, the present study's results reveal that grizzly bears experience a vegetation‐associated drawdown of POPs previously acquired through the consumption of salmon, to such an extent that net biomagnification is reduced. Environ. Toxicol. Chem. 2013;32:995–1005. © 2013 SETAC